2016
DOI: 10.1158/1055-9965.epi-15-0894
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory-Related Genetic Variants in Non–Muscle-Invasive Bladder Cancer Prognosis: A Multimarker Bayesian Assessment

Abstract: Background: Increasing evidence points to the role of tumor immunologic environment on urothelial bladder cancer prognosis. This effect might be partly dependent on the host genetic context. We evaluated the association of SNPs in inflammationrelated genes with non-muscle-invasive bladder cancer (NMIBC) risk-of-recurrence and risk-of-progression.Methods: We considered 822 NMIBC included in the SBC/ EPICURO Study followed-up >10 years. We selected 1,679 SNPs belonging to 251 inflammatory genes. The association … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…A total of 10 genes were identified to be correlated with overall survival. Among these identified genes, 5 genes (CALD1, HOXB3, HOXB6, MOGAT2, and TNC) have been reported to be associated with the development or prognosis of bladder cancer, indicating that the results in our study are consistent with previous publications in bladder cancer [ 29 31 ]. The remaining 5 genes have not been found to be associated with the prognosis of bladder cancer (BTBD16, OLFML2B, PRRX1, SPINK4, and SPON2).…”
Section: Discussionsupporting
confidence: 92%
“…A total of 10 genes were identified to be correlated with overall survival. Among these identified genes, 5 genes (CALD1, HOXB3, HOXB6, MOGAT2, and TNC) have been reported to be associated with the development or prognosis of bladder cancer, indicating that the results in our study are consistent with previous publications in bladder cancer [ 29 31 ]. The remaining 5 genes have not been found to be associated with the prognosis of bladder cancer (BTBD16, OLFML2B, PRRX1, SPINK4, and SPON2).…”
Section: Discussionsupporting
confidence: 92%
“…This protein may be involved in cell growth and differentiation and it is known as a negative regulator of T-and B-cell receptor signaling. Its expression has been shown to be implicated in T lymphocytes tolerance toward tumor cells [49]. In contrast we have found that genetic variations in BLNK (rs3789928), TP63 (rs710521), ROCK1 (rs288980) and ACTRT3/MYNN (rs10936599) were associated with a decreased risk of bladder cancer.…”
Section: Others Cellular Pathwaymentioning
confidence: 63%
“…Previous studies have reported that inflammation-associated genes risk signature can be used to predict patient prognosis and guide treatment for esophageal squamous cell carcinoma, lung adenocarcinoma and urothelial bladder cancer. [28][29][30][31] Other hand, Sia et al determined that inflammation response-related gene signature could be correlated with the immune exhausted. 32 Many cancers are characterized by simultaneous immunosuppression and inflammation, their regulation is integrally linked, which can induce a dysfunctional immune state unable to eliminate disease.…”
Section: Discussionmentioning
confidence: 99%